Detection by Flow Cytometry of Anti-DNA Autoantibodies and Circulating DNA Immune Complexes in Lupus Erythematosus. (5th December 2019) - Abuaf, Nisen; Desgruelles, Chantal; Moumaris, Mohamed; Boussa-Khettab, Faïza; Rostane, Hidayeth; Bellec, Emilie; Frances, Camille
Abstract : A new method for the detection by flow cytometry of anti-double-stranded DNA antibodies and of circulating immune complexes (IC) containing endogenous DNA (IC-eDNA) is described. From each serum sample, two samples were taken, one was used to detect IC-eDNA. The other to detect anti-DNA antibodies was incubated with calf thymus DNA. ICs were isolated by polyethylene glycol precipitation or by cryoprecipitation, after which immunoglobulins were labeled with FITC-conjugated anti-human globulin. Serum samples from 63 systemic lupus erythematosus (SLE) patients, 32 incomplete lupus, and 87 control patients were tested. Detection of anti-dsDNA antibodies by flow cytometry had a diagnostic sensitivity and specificity almost comparable to routine tests, the fluorescent enzyme immunoassay EliA™-dsDNA test, and the ultrasensitive Crithidia luciliae indirect immunofluorescence test. In 21 (33%) out of 63 SLE serum samples, IC-eDNA was detected. In these samples, free anti-dsDNA antibodies were hardly detectable or undetectable by flow cytometry or by routine tests. When anti-DNA antibodies are neutralized by endogenous DNA and can no longer be detected by routine tests, the serologic diagnosis and the follow-up of relapses in patients with SLE is compromised. To overcome this obstacle, we propose an accessible solution: the detection of circulating IC-eDNA by flow cytometry.